2018
DOI: 10.1186/s12915-018-0535-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of village dog and wolf genomes highlights the role of the neural crest in dog domestication

Abstract: BackgroundDomesticated from gray wolves between 10 and 40 kya in Eurasia, dogs display a vast array of phenotypes that differ from their ancestors, yet mirror other domesticated animal species, a phenomenon known as the domestication syndrome. Here, we use signatures persisting in dog genomes to identify genes and pathways possibly altered by the selective pressures of domestication.ResultsWhole-genome SNP analyses of 43 globally distributed village dogs and 10 wolves differentiated signatures resulting from d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
157
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 191 publications
3
157
1
Order By: Relevance
“…Domestication of course involves genetic changes . Regulatory regions were found to differ much more than coding sequences in genomic studies of domestication in rabbits and dogs . Genomic tools are being used to test whether domestication features “resulted from a relaxation of selection as animals exited the wild environment or, alternatively, from positive selection resulting from conscious or unconscious human preference” (Larson and Fuller, p. 127–128).…”
Section: Morphology and Human Self‐domesticationmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestication of course involves genetic changes . Regulatory regions were found to differ much more than coding sequences in genomic studies of domestication in rabbits and dogs . Genomic tools are being used to test whether domestication features “resulted from a relaxation of selection as animals exited the wild environment or, alternatively, from positive selection resulting from conscious or unconscious human preference” (Larson and Fuller, p. 127–128).…”
Section: Morphology and Human Self‐domesticationmentioning
confidence: 99%
“…Many of these features derive from the neural crest, discussed below . Indeed, inspired by the suggestion of neural crest as a driver of morphological patterns associated with domestication, several recent genomic studies of the domestication of dogs, cats, rabbits, and horses reported evidence for positive selection on genes involved in neural crest “development programs.” In addition, hormonal changes—potentially related to the neural crest—have been at the center of the HSD hypothesis. Cieri et al hypothesized an enhanced social tolerance since the Middle Pleistocene, physiologically caused by a reduction in average androgen reactivity and morphologically expressed in craniofacial feminization.…”
Section: Introductionmentioning
confidence: 99%
“…Such a secondary effect can occur if human-directed play behaviour is a component of the domestication syndromes(Darwin, 1868;Wheat, Fitzpatrick, Rogell, & Temrin, 2019;Wilkins, Wrangham, & Fitch, 2014) whereby an entire suite of traits enhancing the bond between owners and their dogs are genetically linked and thus collectively respond to existing artificial selection on function. Wolf-dog hybrids are considerably less playful with humans than dogs in general indicating that the human-directed playfulness was not or little expressed in the undomesticated wild ancestors(Burghardt, 2005;Pendleton et al, 2018;Wheat et al, 2018). However, several ancient breeds that likely reflect early states of domestication(Wheat et al, 2019) were characterized by intermediate average scores for human-directed playfulness (e.g.…”
mentioning
confidence: 99%
“…At present, modified NCC functioning provides the most widely supported explanation for the observed link between selection for reduced aggression and the wider syndrome of domesticated traits (Geiger et al, 2018;Montague et al, 2014;Pendleton et al, 2018;Wilkins, 2017;Wilkins et al, 2014;Zeder, 2017). Wilkins et al (2014) proposed that hypoplasia of the NCC-derived adrenal medulla dampens behavioural reactivity prompted by the Hypothalamic-Pituitary-Adrenal (HPA) axis.…”
mentioning
confidence: 99%